Cine MRI detects elevated left heart pressure in pulmonary hypertension. Issue 1 (9th January 2021) - Lin, Kai; Sarnari, Roberto; Pathrose, Ashitha; Gordon, Daniel; Blaisdell, Julie; Markl, Michael; Carr, James C.
Abstract: Cine magnetic resonance imaging (MRI) is an emerging modality for evaluating left ventricular (LV) motion/deformation patterns, which may have potential to identify LV dysfunctions underlying postcapillary pulmonary hypertension (PH). The aim of this study was to test the hypothesis that cine MRI‐derived LV motion/deformation indices can be used to identify an elevated left heart pressure in PH. This was a retrospective study, which included 26 precapillary and 28 postcapillary PH patients (23 males, 58.9 ± 13.5 years old). All patients underwent right heart catheterization (the "reference standard") and cardiac MRI. Balanced steady‐state free precession cine sequence acquired at 1.5 T was used. Cine MRI datasets were analyzed by using heart deformation analysis. LV motion/deformation indices were measured through 25 phases within a cardiac cycle. Peak LV displacement, velocity, strain, and strain rates at systole, early and late diastole were compared between the two patient groups using t ‐tests. The Pearson correlation coefficient ( r ) was used to investigate the association between cine MRI‐derived indices and pulmonary capillary wedge pressure (PCWP). Multivariable linear and logistic regression models were applied to assess the ability of MRI‐derived parameters to predict PCWP and postcapillary PH. Compared to 26 precapillary PH patients, the 28 postcapillary PH patients had lower peak late radial diastolic displacement (0.43 ± 0.19 cm vs. 0.64 ± 0.18 cm) and velocity (12.2 ± 5.8 mm/s vs. 18.9 ± 5.6 mm/s) and peak late radial (52.1 ± 32.7%/s vs. 97.1 ± 38%/s) and circumferential (38 ± 19.8%/s vs. 63.1 ± 22.9%/s) strain rates. PCWP was correlated with peak late radial diastolic displacement ( r  = −0.54) and velocity ( r  = −0.57) and peak late radial ( r  = −0.63) and circumferential diastolic ( r  = −0.63) strain rates. Peak late radial strain rate could predict PCWP ( β  = −0.09) and postcapillary PH ( β  = −0.036). All p  < 0.05. Cine MRI‐derived LV late diastolic motion/deformation properties can be used to estimate elevated left heart pressure in PH. Level of Evidence: 3 Technical Efficacy Stage: 1